The use of management control and performance measurement systems in SMEs: A levers of control perspective - Pešalj, Biljana; Pavlov, Andrey; Micheli, Pietro (Emerald, 2018)
Purpose The purpose of this paper is to respond to recent calls for understanding how multiple management control (MC) and performance measurement (PM) systems are used simultaneously for managing performance, particularly in the context of small- and medium-sized enterprises (SMEs). Design/methodology/approach Data are collected during an in-depth case study of MC and PM and management practices in a Dutch SME using multiple data sources and elicitation methods, including interviews and participant observations. Findings This study identifies managerial practices that enable the interplay of the four control systems – beliefs, boundaries, diagnostic and interactive – helping the organization manage organizational tensions in relation to short- and long-term focus, predictable goal achievement and search for new opportunities, internal and external focus, and control and creativity. Research limitations/implications This paper advances the research on integrating multiple aspects of performance management, particularly technical and social. This research is based on a single case study; future qualitative and quantitative studies could explore the interplay between the four control systems in other settings and explore the relationship between control systems and leadership style. Practical implications Managing performance requires active and continuous use of all four control systems. This is particularly salient in SMEs where less formal controls play a key role and where balance needs to be ensured despite the lack of managerial processes and capabilities. Originality/value The findings advance PM and management theory and practice in the context of SMEs.
Keywords: Lean manufacturing organisations; lean production; literature review; management control; performance management